1990
DOI: 10.1128/jvi.64.3.1207-1216.1990
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and partial characterization of an unusual human immunodeficiency retrovirus from two persons of west-central African origin

Abstract: An unusual human retrovirus was isolated from two patients with persistent generalized lymphadenopathy who originate from West-Central Africa and are currently residing in Belgium. Although the virus shared a number of the same biological and morphological properties as human immunodeficiency retrovirus type 1 (HIV-1) and HIV-2, significant antigenic differences could be demonstrated. Several of the viral proteins also differed in molecular weight from the corresponding HIV-1 and HIV-2 proteins. Partial chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(42 citation statements)
references
References 38 publications
(32 reference statements)
1
41
0
Order By: Relevance
“…2). The PERT assay thus compares well with the most sensitive sequence-specific methods described by others [Piatak et al, 1993;Bruisten et al, 1993;Ho et al, 19951. In contrast to sequence-specific procedures, whose sensitivity may be hampered by genomic variability, as is the case for HIV-1 subtype 0 infection [De Leys et al, 1990;Giirtler et al, 1994;van den Haesevelde et al, 19943, the PERT Assay is not affected adversely Fig. 4.…”
Section: Discussionmentioning
confidence: 99%
“…2). The PERT assay thus compares well with the most sensitive sequence-specific methods described by others [Piatak et al, 1993;Bruisten et al, 1993;Ho et al, 19951. In contrast to sequence-specific procedures, whose sensitivity may be hampered by genomic variability, as is the case for HIV-1 subtype 0 infection [De Leys et al, 1990;Giirtler et al, 1994;van den Haesevelde et al, 19943, the PERT Assay is not affected adversely Fig. 4.…”
Section: Discussionmentioning
confidence: 99%
“…The couple infected by the HIV-1 group O virus described in this study was first identified in 1987 [De Leys et al, 1990]. The nucleotide sequence of the virus (a prototype of HIV-1 group O) has previously been fully analyzed [De Leys et al, 1990;Vanden Haesevelde et al, 1994], and represents the prototype of HIV-1 group O viruses.…”
Section: Case Reportsmentioning
confidence: 99%
“…These viruses are characterized by extensive alteration in their nucleotide sequence [Wong-Staal et al, 1995]. As a consequence, HIV-1 isolates have been subdivided into group M with at least eight genetic subtypes (A through H) [Myers et al, 1993] and group O [De Leys et al, 1990;Gurtler et al, 1994;Vanden Haesevelde et al, 1994]. HIV-1 group O isolates are highly divergent from group M isolates, differing by about 50-60% in the env gene Vanden Haesevelde et al, 1994].…”
Section: Introductionmentioning
confidence: 99%
“…HIV is one of the best examples of how the analysis of genetic data can be used to understand the history and dynamics of emergence over multiple timescales. Phylogenetic analyses of HIV-1, HIV-2, and multiple SIVs have (a) revealed a western African origin for HIV, (b) identified chimpanzee subspecies Pan troglodytes troglodytes as the reservoir of HIV-1 and the sooty mangabey (Cercocebus atys) as the reservoir of HIV-2, and (c) inferred that the emergence of the prominent global variant of HIV-1, group M subtype B, originated from a single migration event out of Haiti around 1970 (26,46,51,68,126). The reconstruction of contact networks using genetic data has also proved successful, revealing multiple webs of transmission linked by risk factor (e.g., hemophiliacs, heterosexuals, intravenous drug users, men who have sex with men) and migration pattern (9,60,80,84).…”
Section: Inferring the Origin And Dynamics Of Emerging Pathogens Frommentioning
confidence: 99%